Kecenderungan melakukan unsafe abortion pada perempuan dengan kehamilan tidak diinginkan di Yogyakarta - Farida Nur Aini; Endah Marianingsih Theresia; Yuliasti Eka Purnamaningrum (Jurnal Kesehatan Ibu dan Anak, 2013)
Annually in Indonesia millions of women had an unplanned pregnancy and often looking for help to an abortion through nonmedical personnel who use the ways that endanger to abort the pregnancy. To describe the tendencies of unsafe abortion on women with unwanted pregnancies. This research uses qualitative phenomenological methods with respect to unsafe abortion phenomenon that occurred in Yogyakarta. This research was conducted in Yogyakarta city. Informants surveyed is female between 15-34 years with pregnancy undesirable who performs unsafe abortion to end her pregnancy and companion of the women (husband or fiends). The sampling technique used was snowballing sampling using the gatekeepers. Methods of data collection using in-depth the interview, observation unstructured, and methods of the documentary. Data analysis using life history analysis. Informant A, D, and I perform unsafe abortion because of unwanted pregnancy. Methods used variously, ranging from young pineapple juice mixed drink beer with stomach massage and takes the pill purchased from advertising late menstruation that is much found in the streets. Informants tend to do unsafe abortion because lt is the fastest ways in terminate a pregnancy by relatively cheap and affordable cost. Women with unwanted pregnancies tend to do unsafe abortion because it proved effective enough to terminate the pregnancy and cheap and easy to reach.